STRATEGIES IN ENGLISH ACADEMIC WRITING USED BY INDONESIAN GRADUATE STUDENTS IN HUNGARIAN HIGHER EDUCATION - Subandowo, Dedy (Sinergi Aksi Inovasi Budaya Menulis Inspiratif, 2024)
The purpose of this paper is to discover the strategies that Indonesian graduate students use when writing academic texts, such as essays. The study aims to identify effective writing strategies that can enhance the academic performance of Indonesian graduate students. To accomplish the objective, the investigation focused on the writing strategies utilized by the students when writing academic essays in English. The study utilized qualitative methods to collect data by conducting semi-structured interviews on the writing process. Ten graduate students from five universities in Hungary participated in the study. The interview transcription used in the study applied the Google Speech API demonstration. The transcriptions were uploaded to Atlas.Ti, a software used for qualitative data analysis, in order to conduct further examination and perform codification and categorization. The findings suggest that the students utilize writing strategies including drafting and brainstorming, conducting preliminary research, engaging in extensive reading, taking notes, utilizing Google Translate for Indonesian to English translation, employing writing tools, enhancing clarity, evaluating the text (e.g., refining ideas, developing content), revising (e.g., correcting minor errors), and finalizing (e.g., thoroughly checking for mistakes, ensuring proper layout and referencing).